High-value Market Channels and Their Implications for the Actors of Pineapple Value Chain in Sri Lanka - Ganepola, G. A. U. M.; Wickramasinghe, A. A. M. D.; Udagedara, G.; Fernando, S.; Kopiyawattage, K. P. P. (University of Jaffna, 2024)
Access to high-value markets is one of the major challenges faced by the smallholder producers in developing countries. The study applies value chain analysis to the pineapple sub-sector in Sri Lanka to identify ways of improving the access of smallholder farmers to the global fresh pineapple market since it has a fast-growing export demand. The value chain analysis was carried out to identify its nature, actors, and sources of inefficiency along the value chain. The study employed a qualitative research design, and structured and unstructured interviews were held, respectively, with 30 farmers and 5 exporters. Study shows that pineapple production is dominated by smallholder farmers with limited access to information (export price, quality, and standard), healthy and quality planting materials, inputs such as fertilizer, credit and technology (best practices), and a short supply of lands with unique soil properties favorable to cultivate pineapple. Low productivity, high cost of production, and quality reduction of pineapple (reduction in fruit size) in subsequent harvests after the first crop drained farmers’ competitiveness. Irregularity of payments and time taken to settle dues by collectors on the other hand deteriorated farmers’ trust. On the other hand, the competitiveness of the exporters on the other hand was undermined by the upsurge of export tax and lack of a reliable supply of quality consistent fruits in adequate quantities. Policy interventions are required to develop market institutions for smallholders, such as producer societies, cooperatives, contract farming, or out-grower schemes. Moreover, revitalizing the extension service to transfer the specific knowledge required to produce export-quality pineapples, organizing credit schemes to provide operational capital to both farmers and collectors and conducting research on development of planting materials and varieties would improve the efficiency along the chain.
Keywords: Export market; Pineapple; Small holder farmer; Sri Lanka; Value chain